Efek Perlindungan Susu Kedelai (Glycine max) Ultra High Temperature (UHT) Terhadap Lambung Mencit - Wijnaputri, Ginong Pratidina; Listyaningsih, Endang; Subandono, Jarot (Nexus Biomedika, 2012)
Background: White Soybean (Glycine max) Milk Ultra High Temperature (UHT) is potential to protect gaster because it contains flavonoid. This study aimed to investigate the protective effect of white soybean milk UHT on miceâs gaster due to aspirin. Higher dose of the milk reduces the damaged on gastric mucous induced by aspirin Methods: This was a labroratory experimental research with posttest only controlled group design conducted in in Histology Laboratory of Sebelas Maret University. The samples were thirty five mice divided into 5 groups. Negative control group (KN) was given normal food and aquadest, positive control group (KP) was given aspirin dose 2,275 mg/20g Body weight (W), dan first treatment group (P1) was given cimetidine dose 0,78 mg/20g W second treatment group (P2) and third treatment group (P3) was given soybean milk UHT dose 0,7ml/20 g W and 1,4 ml/20 g W. All treatments for KN, KP, P1 , P2, P3 was given in 10 days. Aspirin was given to KP, P1 , P2, P3 with dose 2,275 mg/20g weight of mice on day 8, 9 and 10. to evaluate theÂ level of damage based on histologic appearance, gastric staining was performed using Haem eos. Results: Kruskal-Wallis test result showed significant result among four groups. Mann-Whitney showed significant result for KN compared to KP,P1,P2 , P3 and KP compared to P1, P2 and P3 ; while P1 compared to P2, P3 and P2 compared to P3 had no significant result. Conclusion: White Soybean (Glycine max) Milk Ultra High Temperature(UHT) protect miceâs gastric from gastritis. However, higher dose of White Soybean (Glycine max) Milk Ultra High Temperature(UHT) does not increase the protective effect of white soybean milk UHT on miceâs gaster due to aspirin. Keywords: White Soybean (Glycine max) Milk Ultra High Temperature(UHT), gastric protection, gastritis, aspirin.Â